Exercise Training in Patients With Heart Failure and Preserved Ejection Fraction. (January 2015) - Pandey, Ambarish; Parashar, Akhil; Kumbhani, Dharam J.; Agarwal, Sunil; Garg, Jalaj; Kitzman, Dalane; Levine, Benjamin D.; Drazner, Mark; Berry, Jarett D.
<x xml:space="preserve">Abstract</x> Background— Heart failure with preserved ejection fraction (HFPEF) is common and characterized by exercise intolerance and lack of proven effective therapies. Exercise training has been shown to be effective in improving cardiorespiratory fitness (CRF) in patients with systolic heart failure. In this meta-analysis, we aim to evaluate the effects of exercise training on CRF, quality of life, and diastolic function in patients with HFPEF. Methods and Results— Randomized controlled clinical trials that evaluated the efficacy of exercise training in patients with HFPEF were included in this meta-analysis. Primary outcome of the study was change in CRF (measured as change in peak oxygen uptake). Effect of exercise training on quality of life (estimated using Minnesota living with heart failure score), and left ventricular systolic and diastolic function was also assessed. The study included 276 patients who were enrolled in 6 randomized controlled trials. In the pooled data analysis, patients with HFPEF undergoing exercise training had significantly improved CRF (mL/kg per min; weighted mean difference, 2.72; 95% confidence interval, 1.79–3.65) and quality of life (weighted mean difference, −3.97; 95% confidence interval, −7.21 to −0.72) when compared with the control group. However, no significant change was observed in the systolic function (EF−weighted mean difference, 1.26; 95% confidence interval, −0.13% to 2.66%) or diastolic function (E/A−weighted mean difference, 0.08; 95% confidence interval, −0.01 to 0.16) with exercise training in patients with HFPEF. Conclusions— Exercise training in patients with HFPEF is associated with an improvement in CRF and quality of life without significant changes in left ventricular systolic or diastolic function.